Kebijakan Deviden dalam Memediasi Faktor yang Mempengaruhi Nilai Perusahaan - Kodriyah, Kodriyah; Mahardini, Nikke Yusnita; Malik, Abdul; Wulandari, Maudi (Penerbit Goodwood, 2025)
Purpose: With dividend policy acting as an intervening variable, this study intends to investigate the impact of leverage and investment opportunity set on firm value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2016 and 2022. Research methodology: The sample method used is purposive sampling, with a total of 122 companies as samples. The analysis method of this research uses path analysis and is processed using SPSS 25 tools. Results: The findings indicate that the following factors affect firm value: leverage, investment opportunity set, and dividend policy. Leverage has no effect on firm value, while investment opportunity set has an impact on dividend policy. Additionally, dividend policy cannot be an intervening variable between leverage and investment opportunity set. Conclusions: The study concludes that leverage significantly influences firm value, as companies with higher debt levels are perceived to have greater future growth prospects. Investment opportunity set also positively affects firm value, indicating that broader investment opportunities enhance returns and increase firm value. However, dividend policy neither directly influences firm value nor mediates the relationship between leverage or investment opportunity set and firm value. Limitations: Limited research proves the effect of leverage, Investment Opportunity Set, and devidend policy as mediating variables on firm value. Contribution: This research contributes to investors' understanding that if they want to invest, they should look at the company's prospects through firm value. Companies must be considered from an investor's perspective, including the level of debt and Investment Opportunity Set, if they want to be considered good.